2015
DOI: 10.1038/srep09392
|View full text |Cite
|
Sign up to set email alerts
|

The Association of GSTM1 Deletion Polymorphism with Lung Cancer Risk in Chinese Population: Evidence from an Updated Meta-analysis

Abstract: Previous studies have reported the association of glutathione S-transferase M1 (GSTM1) deletion polymorphism with genetic susceptibility of lung cancer in Chinese population. However, the results remained controversial. The aim of this study was to clarify the association of GSTM1 deletion polymorphism with lung cancer risk in Chinese population. Systematic searches were performed through the search engines of Medline/Pubmed, Web of Science, EMBASE, CNKI and Wanfang Medical Online. The pooled effects were calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 48 publications
1
22
0
1
Order By: Relevance
“…GROM predicted a deletion spanning the entire RHD gene, 1 of 2 genes responsible for Rh blood group antigens [ 30 ]. Decreased copy numbers or null genotype of GSTM1 have been associated with hepatotoxicity [ 31 ] and higher risk of many cancers including lung cancer [ 32 ], gastric cancer [ 33 ], and bladder cancer [ 34 ]. UGT2B17 copy number variation has been associated with changes in bone mineral density and risk of osteoporosis [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…GROM predicted a deletion spanning the entire RHD gene, 1 of 2 genes responsible for Rh blood group antigens [ 30 ]. Decreased copy numbers or null genotype of GSTM1 have been associated with hepatotoxicity [ 31 ] and higher risk of many cancers including lung cancer [ 32 ], gastric cancer [ 33 ], and bladder cancer [ 34 ]. UGT2B17 copy number variation has been associated with changes in bone mineral density and risk of osteoporosis [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Studies also showed that in smokers, there is higher risk of lung cancer for GSTM1 deficient type compared with GSTM1 functional type. This implies that either smoking and GSTM deficiency have a synergistic effect, or that both are risk factors of lung cancer; additionally, smoking subjects who carrying GSTM1 deficient would have an increased risk of lung cancer. This phenomenon could be explained by the fact that some procarcinogens (such as polycyclic aromatic amines (PHA) in cigarettes, 4,5 epoxidation benzo a pyrene (BaPo)) that are activated by phase I metabolic enzymes are substrates of GSTM1; GSTM1 plays an important role in the metabolic inactivation of these carinogens.…”
Section: Discussionmentioning
confidence: 99%
“…Studies also showed that in smokers, there is higher risk of lung cancer for GSTM1 deficient type compared with GSTM1 functional type. This implies that either smoking and GSTM deficiency have a synergistic effect, or that both are risk factors of lung cancer 25,26 ;…”
Section: On Mongolian and Han Populations In The Inner Mongolianmentioning
confidence: 99%
“…Numerous studies of GSTM1 CNVs have been conducted following the discovery of the common null genotype as an early risk factor for some forms of cancer [Yang et al, ]. Furthermore, several studies have investigated relationships between the GSTM1 null genotype and schizophrenia.…”
Section: Discussionmentioning
confidence: 99%